Pregnancy and delivery after augmentation enterocystoplasty: a case report - Bobelytė, Odeta; Jankevičius, Feliksas; Paliulytė, Virginija; Manikas, Martynas; Ramašauskaitė, Diana (Acta medica Lituanica, 2014)
Background. The aim of this article is to present a rare clinical case of pregnancy and surgical delivery after bladder augmentation surgery in the past. Methods and materials. In this report we present one case of a 23-yearold woman who became pregnant 3 years later after bladder augmentation surgery for congenital microcystis leading to hydronephrosis and nephrosclerosis and delivered a live healthy baby through a lower segment Caesarean section at 38 weeks of gestation in Vilnius University Hospital Santariškių Clinics. We investigated all documentation of the patient before and after bladder augmentation enterocystoplasty. Results and conclusions. Bladder augmentation is mostly performed for women in their childhood or young age and most of them reach reproductive age. There is no contraindications for these women to become pregnant and deliver, both vaginally or surgically. It is advisable to consult urologists regularly, make regular bacteriological urine analysis, take monthly blood samples for kidney function evaluation and perform renal ultrasonography. Multiple consultations in a Perinatology Center are also necessary to follow the fetus condition and prevent preeclampsia. Antibacterial treatment or prophylaxis should be used during pregnancy if necessary, intermittent self-catheterization is mostly performed routinely. The presence of a urologist is suggested during the Caesarean section.
Keywords: augmentation cystoplasty; pregnancy; Caesarean section; delivery